"Eu já fui arrancado de vários lugares. Arrancado. E ainda tenho um pedacinho e para eu sair de lá vou ter que sair arrancado também". Extrahección e Resistência em Conceição do Mato Dentro - MG - Yasmin Rodrigues Antonietti (2019)
The arrival and installation of a large mining project, the Minas-Rio, in Conceição do Mato Dentro (MG), resulted in permanent and deep changes in the life, dwelling and work of many rural communities present in the municipality. In this sense, the main objective of the present work is to understand the entrepreneur's strategies regarding the acquisition of land, as well as its effects on those affected, starting from the macro scenario of the adoption of a neo-extractive development model by most South American countries to the reproduction of expropriatory processes at local levels and their multidimensional effects. The reflection, made through qualitative and quantitative methodologies, in the first moment, starts from the disputes around the different forms of appropriation of space so that, afterwards, the specific case of the Minas-Rio in Conceição do Mato Dentro, analyzing and characterizing, historically, the strategies of land acquisition adopted by the mining company, the dispute between different actors during the environmental licensing process and their effects on the livelihoods and occupation of the region. Therefore, strategies such as the use of an orange company to reduce prices, non-recognition of the universe of the affected people, pressures on groups and families, weakening of family and neighboring ties, disregard and sometimes negation of traditional forms were highlighted resulting in a conflict of large proportions.